Pleasure and Happiness Relationship in Ibn Sina and Epicureans - Maryam Afshar; Mohammad Raayat Jahromi (حکمت سینوی)
The central issue of this paper is to explain the place of pleasure and happiness and their relationship in the thought of Ibn Sina and Epicurus, and to conduct a comparative study of these concepts. For this purpose, using a descriptive-analytical method and library sources, we will examine the Epicurean approach to pleasure and happiness, with a focus on superior pleasure, the four-part cure, and the various dimensions of their hedonism and sensualism. In fact, Epicureans consider the primary goals of moral theory to be describing the nature of happiness and outlining the methods to achieve it. In the case of Ibn Sina, we will explore superior pleasure and types of happiness in his philosophy, drawing on his teleology and focusing on the concept of perception. Ibn Sina connects happiness to specific types of pleasure. Finally, since Epicurus and Ibn Sina present unique concepts of pleasure and happiness based on different worldviews, we will conduct a comparative analysis focusing on virtue-oriented approaches and perception, because both philosophers emphasize the central role of ethics and virtue in the pursuit of happiness. Based on the aforementioned points, this paper compares the views of Epicureans and Ibn Sina on pleasure and happiness.